Art and print production - Sarkar, N.N. (Oxford University Press, 2008)
This book is practical in its approach and addresses the requirements of students and practitioners. It identifies and defines their problems concretely, analyzes and suggests the solutions thereto, adapted to local needs, tastes and perceptions. A unique feature of this book is the treatment of the subject in the context of its applicability and the technology available in India at present or in the foreseeable future. This book will be extremely useful to students as well as practising executives in taking logical, result-oriented decisions on design selection